A safety signal of somnambulism with the use of antipsychotics and lithium: A pharmacovigilance disproportionality analysis. Issue 10 (27th March 2021) - Gouverneur, Amandine; Ferreira, Amandine; Morival, Camille; Pageot, Cécile; Tournier, Marie; Pariente, Antoine
Abstract : Aims: Antipsychotics and lithium are widely used in psychiatry, particularly in schizophrenia and bipolar disorders. Recently, some cases of somnambulism or sleep‐related eating disorder (SRED) have been reported in patients treated with these drugs. This study investigated the risk of reporting somnambulism or SRED associated with the use of antipsychotics and lithium. Methods: The World Health Organization pharmacovigilance database (VigiBase), comprising >18 million adverse events, was queried. All somnambulism or SRED reports related to antipsychotics or lithium were identified. The association between antipsychotics or lithium and somnambulism or SRED was computed using the proportional reporting ratio (PRR) and information component. Results: Among the 5784 cases reporting somnambulism or SRED, 508 suspected at least 1 antipsychotic or lithium. Most patients were aged 18–64 years (62.0%), and 37.0% were men. In most cases (77.6%), antipsychotic or lithium were the only drug class involved, and 53.3% of cases suspected quetiapine. Somnambulism was reported in 88.6% of cases and SRED in 18.1%. A significant association was found for second‐generation antipsychotics (PRR 3.44, 95% confidence interval 3.13) and lithium (PRR 2.03, [1.22; 3.37]), but not for first‐generation antipsychotics (PRR 0.99, [0.68; 1.44]). Conclusions: We found a significant signal of somnambulism or SRED related to second‐generation antipsychotics and lithium. While case reports mentioned mostly quetiapine and olanzapine, almost all second‐generation antipsychotics were associated with somnambulism or SRED.